The Impact of Social Stigma and Self-Esteem on the recidivism to Crime of Sharjah Correctional Prison Inmates - Alnaqbi, Eman; Alomosh, Ahmad (Al-Adab Journal, 2025)
This study aims to determine the effects of social stigma and self-esteem on inmates’ recidivism to crime from their own perspective. The study used the descriptive-analytical approach. A sample of 201 inmates was selected to apply the questionnaire on them. The following results were obtained: The impact of both social stigmatization and self-esteem of the inmates was found to be at a moderate level, with statistically significant differences between the averages of inmates’ responses regarding social stigmatization and self-esteem in favor of social stigmatization. This indicates that society treats inmates harshly and that there is a need to modify its treatment towards prisoners.